1992
DOI: 10.1042/bj2860901
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of lipid peroxidation and hydroxyl-radical generation by the contents of human atherosclerotic lesions

Abstract: Lipid peroxidation within human arterial lesions is thought to play an important role in the development of atherosclerosis. Peroxidation can be accelerated by the presence of 'catalytic' iron or copper ions. Gruel samples from advanced atherosclerotic lesions in the abdominal aortae of human cadavers were tested for pro-oxidant properties. All samples contained bleomycin-detectable iron and phenanthroline-detectable copper. Almost all gruel samples stimulated peroxidation of rat liver microsomes, and this was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
0
4

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 420 publications
(178 citation statements)
references
References 40 publications
6
167
0
4
Order By: Relevance
“…As expected, Chelex-100 removed either copper or iron ions that had been added to Ham's F-10 medium and prevented them from catalysing LDL oxidation. These observations are supported by the work of Smith et al [17] and Swain and Gutteridge [18], who showed that gruel from atherosclerotic lesions contained significant levels of catalytically active copper and iron ions that were able to catalyse the oxidation of rat liver microsomes or linoleic acid micelles.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As expected, Chelex-100 removed either copper or iron ions that had been added to Ham's F-10 medium and prevented them from catalysing LDL oxidation. These observations are supported by the work of Smith et al [17] and Swain and Gutteridge [18], who showed that gruel from atherosclerotic lesions contained significant levels of catalytically active copper and iron ions that were able to catalyse the oxidation of rat liver microsomes or linoleic acid micelles.…”
Section: Discussionmentioning
confidence: 54%
“…It has been demonstrated by Smith et al [17], however, that gruel extracted from advanced atherosclerotic lesions from human aortas can contain significant amounts of catalytically active copper (0-28 /IM) or iron ions (0-7/IM). This finding has very recently been *Corresponding author.…”
Section: Reagentsmentioning
confidence: 99%
“…This model of oxidation was demonstrated to produce LDL sharing many structural and functional properties with LDL oxidized by cells [15] or extracted from atherosclerotic plaques [16]. Moreover, it should be reminded that Cu 2÷ ions are contained in aortic wall and increase in atherosclerotic plaques [3], where they may contribute to the development of the lesion by oxidative stress. On this basis, we suggest that HE (and probably other glycosaminoglycans occurring in native PGs) might play a regulatory role in the process of LDL oxidation in vivo, which may change the metabolic fate of the particle, increasing its atherogenic potential [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Samples of LDL corresponding to 80/.tg cholesterol/ml were then oxidized with 0.9, 1.8 and 3.6/zM CuSO4. These concentrations are in the range originally used by Gieseg and Esterbauer [10] and in the same order of magnitude as those described in atherosclerotic plaques [3]. The oxidation was performed in PBS at 30°C, in the absence and in the presence of HE (varying from 150 to 750/lg/ml, corresponding to 72 362/~g/ml of hexuronate) (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation